To pay more or use less: China’s urban water pricing regime and water awareness - Zhao, B.; Guo, X.; Marinova, Dora (The Modelling and Simulation Society of Australia and New Zealand Inc., 2011)
China is the most populous country in the world. Achieving the country’s sustainability of water resources is vital for its economic development and social wellbeing. China’s shrinking urban water availability has caused worldwide concern for which critics blame the country’s poor water management policies. Recently a water price hike has been unanimously suggested by politicians and international bodies to curb urban water consumption. By reviewing urban water pricing practices and analyzing relevant data for Tianjin City, this paper finds that the water pricing regime in China has not proved to be effective for urban water saving. On the contrary, residents and households in China have been under more financial pressure to bear the brunt of the water crisis. Further problems and challenges associated with water issues and how they impact on China’s policies and strategies are also discussed. Most importantly, by establishing a national sustainability strategy model, this paper suggests that water saving publicity and education can play a key role in easing China’s water crisis. The findings inform policy makers as to how to deal with China’s water shortage while sustaining a quality economic growth.